Global Modeling of N2O Discharges: Helicon Plasma Thruster Application - Konstantinos Katsonis; Chloe Berenguer (International Journal of Aerospace Engineering)
A global (volume averaged) model pertaining to N2O discharges is used to design and to study electric propulsion applications, especially helicon plasma thrusters fed with pure N2O and also with N2/O2 mixtures including air. Results obtained for N2O feeding are discussed and compared to those pertaining to an air-like N2/O2 mixture feeding. An interesting similarity is observed. Comparison of the N2O model results versus those of Ar shows lower ionization percentage with higher electron temperature for N2O propellant.